The Influence Of Foreign & Domestic Institutional Ownership, Board Independence, Audit Quality, Audit Committee, And Stock Liquidity On Cost Of Debt In Indonesian Companies - Deannes, Isynuwardhana (2020)
This study focuses on examining the relationships between corporate governance, stock liquidity, and cost of debt. An extensive literature review indicated that the implementation of corporate governance will reduce the information asymmetry that encourages stock liquidity and lowers the cost of debt. Indonesia, which is classified as an emerging market, has higher interest rates than other ASEAN countries. This can be caused by information asymmetry in the Indonesian capital market. Another factor that can affect the cost of debt is the stock liquidity. Although the price of the Indonesian composite index showed an upward trend, the stock liquidity tended to decrease.